Konsep Bid’ah Menurut Perspektif Muhammadiyah : Kajian Fatwa Majelis Tarjīh dan Tajdīd Muhammadiyah - Fajar Rachmadhani (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
The study entitled "Bid'ah According to the Muhammadiyah Perspective (The Study of Fatwa of the Majelis Tarjih and Tajdid Muhammadiyah" aims to formulate, define and provide more stringent limits on the concept of heresy according to Muhammadiyah through its fatwa institute "Majelis Tarjih and Tajdid" in In the midst of debate about the definition, concept and boundaries of heresy itself, Muhammadiyah wants to offer a moderate definition and concept to become a meeting point of the many schools, schools and religious ideologies that are developing. practically and theoretically, the practical benefits of this research are expected to be able to provide encouragement and motivation to Muslims to always study the vast treasures of Islamic science, so that a moderate Islamic society is realized and always prioritizes tolerance face differences especially the khilafiyah problems. This type of research includes qualitative research. The primary source is a collection of fatwas from the Majelis Tarjih and Tajdid Muhammadiyah. While the secondary sources are data and information derived from fiqh books, fiqh proposals and aqeedah which discuss bid'ah. This study uses the content analysis approach. This method is used to draw conclusions through efforts to bring up the characteristics of messages carried out objectively and systematically.